Characterization of a New Flat Sheet Membrane Module Type for Gas Permeation. Issue 1 (19th November 2018) - Brinkmann, Torsten; Notzke, Heiko; Wolff, Thorsten; Zhao, Li; Luhr, Sebastian; Stolten, Detlef
Abstract: Modern high‐performance flat sheet gas separation membranes exhibit high permeances as well as high selectivities, e.g., for CO2 separation. Novel membrane modules are desirable to transfer the intrinsic membrane performance to the process. The introduced module implements countercurrent flow, which allows for the best utilization of the required driving force, provided concentration polarization and pressure drops can be kept at bay. As such, it is different from established flat sheet modules for gas separation. The design features allow for straightforward scaling and easy adjustment to other operating conditions. During module development equation‐oriented modeling, computer‐aided engineering design and application of computational fluid dynamics for flow optimization were integrated. The prototype was investigated in a pilot plant. The experimental results reflected the simulation predictions and proved the validity of the module concept. Abstract : A flat sheet membrane module for gas separation is introduced. The module implements countercurrent flow patterns and was designed using an integrated process simulation, computer‐aided engineering and computational fluid dynamics approach. The performance of the module prototype was evaluated using pilot‐plant studies.